Forming Learning Independence Through Training On The Use Of Canva In Making E-Books As A Learning Medium For Ppkn In The Independent Curriculum (Wiyatamandala, 2025)
Independent learning is an important skill for students to learn independently and effectively. This study aims to describe the training on the use of canva in creating e-books as a learning media for Pancasila and Civics Education (PPKn) in the Merdeka Curriculum to develop students' independent learning skills. The study used a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results of the study show that training on the use of Canva in creating e-books can help improve students' independent learning skills, such as their ability to organize information, express ideas, improve graphic design, think critically, collaborate, and develop creativity. Additionally, the use of canva can also increase students' interest and motivation in learning PPKn. This study recommends that teachers utilize appropriate technology and learning media that meet students' needs to develop independent learning skills.